VERB IN ENGLISH GRAMMAR SUBJECT - Maryati Salmiah (UIN Sumatera Utara, 2017)
Verb merupakan salah satu dari part of speech. Verbs are words and are one of the elements of part of speech, which denotes the or event or state and attitude. Verb is one of the important elements of various languages including English, so this element gets a special place and more treatment in every grammar. In English itself, verb is a grammar that is much confused by the learners even by native speakers themselves because some of them do not follow the raw form and we can only memorize.